Studies on erythrocyte aminolaevulinate dehydratase I. Its purification and possible therapeutic applications - Bustos, N. (1980)
1. 1. A method for purifying human erythrocytes ALA-D, using a mixture of n-butanol and chloroform, which denature hemoglobin, followed by ammonium sulphate fractionation and affinity chromatography yielding a 1600-fold purified enzyme, is described. 2. 2. By oxidation of Sephadex G-25 with NaIO4, a polyaldehyde, is obtained which can be covalently bound to the ALA-D; however the immobilized enzyme is inactive, because essential ε{lunate}-amino groups at the active site were involved in the coupling. Similar experiments with another enzyme, Rhodanese, resulted in an active insolubilized preparation. 3. 3. By suspending the carrier-enzyme in buffer, slow solubilization with simultaneous release of protein occurs, indicating that this approach might find important therapeutical applications in the treatment of enzyme deficiencies. © 1980.